2013
DOI: 10.1109/twc.2013.022213.112260
|View full text |Cite
|
Sign up to set email alerts
|

Binary Inference for Primary User Separation in Cognitive Radio Networks

Abstract: Abstract-Spectrum sensing receives much attention recently in the cognitive radio (CR) network research, i.e., secondary users (SUs) constantly monitor channel condition to detect the presence of the primary users (PUs). In this paper, we go beyond spectrum sensing and introduce the PU separation problem, which concerns with the issues of distinguishing and characterizing PUs in the context of collaborative spectrum sensing and monitor selection. The observations of monitors are modeled as boolean OR mixtures … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…More explicitly, a substantial security enhancement was achieved by a robust version of the PCA-based method, which exploited the sparse, low-rank nature of the auto-covariance matrices of the smart metering signal and of the wideband interferer, respectively, in order to confidently separate them prior to ICA processing. Another pertinent example is found in cognitive radio scenarios, where the so called Boolean ICA relied on the Boolean mixing of OR, XOR, and other functions of binary signals [12]. It was also incorporated into the PU separation problem often encountered in cognitive radio networks for the sake of distinguishing and characterizing the activities of PUs in the context of collaborative spectrum sensing.…”
Section: K-means Clustering: Heterogeneous Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…More explicitly, a substantial security enhancement was achieved by a robust version of the PCA-based method, which exploited the sparse, low-rank nature of the auto-covariance matrices of the smart metering signal and of the wideband interferer, respectively, in order to confidently separate them prior to ICA processing. Another pertinent example is found in cognitive radio scenarios, where the so called Boolean ICA relied on the Boolean mixing of OR, XOR, and other functions of binary signals [12]. It was also incorporated into the PU separation problem often encountered in cognitive radio networks for the sake of distinguishing and characterizing the activities of PUs in the context of collaborative spectrum sensing.…”
Section: K-means Clustering: Heterogeneous Networkmentioning
confidence: 99%
“…In [14] the authors presented a heterogeneous fully distributed multi-objective strategy based on a reinforcement learning model con- Spectrum learning in cognitive radio [12] figure 3. Illustration of reinforcement learning: a) Markov decision process; b) partially observed Markov decision process; c) Q-learning.…”
Section: Q-learning: Femto/small Cellsmentioning
confidence: 99%
“…Hence its cancellation requires at least 120 dB interference rejection. Furthermore, in [265], the Boolean ICA concept was proposed based on the integration of Boolean functions of binary signals for inferring the activities of the underlying latent signal sources. Specifically, it was shown that given m SUs, the activities of up to (2m − 1) PUs can be determined.…”
Section: a N M ] T Furthermore Letmentioning
confidence: 99%
“…The errors in the noisy cases can be attributed to the fact that the average PU active probability is around 2%, which is comparable to the noise level. More information on this application can be found in [22].…”
Section: Number Of Pus Prediction Error On Y (%)mentioning
confidence: 99%